2015
DOI: 10.7439/ijbr.v6i6.2103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatitis B virus infection in pregnant women

Abstract: Background: Hepatitis B virus infection is a major public health problem around the globe in spite of the availability of a highly effective vaccine and improvements in antiviral therapy. This disease causes a chronic hepatitis, liver cirrhosis and hepatocellular carcinoma. Patients and methods:The cross sectional study consisted from 40 healthy pregnant females referred to privet clinic for primary health care for pregnant women in Baghdad from September 2010-to May 2011.Their bloods were analyzed for hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In Iraq, a case-control study done in Baghdad on 40 pregnant females visiting private-sector hospital in 2010-2011 showed HBsAg to be 5% [28]. However, another study done in primary health centers on 6975 pregnant females in 2016-2017 found HBsAg prevalence to be 0.13% [29].…”
Section: Central Asia (Afghanistan Kazakhstan Kyrgyzstan Tajikistan T...mentioning
confidence: 99%
“…In Iraq, a case-control study done in Baghdad on 40 pregnant females visiting private-sector hospital in 2010-2011 showed HBsAg to be 5% [28]. However, another study done in primary health centers on 6975 pregnant females in 2016-2017 found HBsAg prevalence to be 0.13% [29].…”
Section: Central Asia (Afghanistan Kazakhstan Kyrgyzstan Tajikistan T...mentioning
confidence: 99%
“…Infection due to Hepatitis B virus is a serious public health problem worldwide, in spite of the availability of a highly potent vaccine and upgrade in antiviral therapy [1].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the arrival of anti-viral therapies that can conquer HBV and delay advancement of liver disease, most people with chronic HBV infection live in developing countries where these drugs are neither cheap nor accessible, the incidence of HBV-related HCC cases is projected to increase for at least two decades due to the high prevalence of chronic HBV infection throughout the world [9]. HBV is mostly contracted at birth and early childhood [8], it is transmitted vertically from infected mother to child during delivery and horizontally through sexual intercourse [1]. Vertical transmission from an infected mother to her baby is common through the placenta, about 90% get infected during the prenatal period [10].…”
Section: Introductionmentioning
confidence: 99%